2016
DOI: 10.1177/1081286516635871
|View full text |Cite
|
Sign up to set email alerts
|

The frictionless axial interaction of a rigid disk with a two-layered functionally graded transversely isotropic medium

Abstract: A rigorous formulation is presented for the frictionless axisymmetric interaction of a rigid disk with a two-layered inhomogeneous medium. The materials are considered to be linearly elastic transversely isotropic materials and the exponential variation of properties along the depth of each layer is assumed in order to model the effect of inhomogeneity. The disk is considered to be at the top of the coating layer or embedded at the interface of the two media. By satisfying the boundary conditions, the problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Akbari et al [31] examined the static response of exponentially graded transversely isotropic substrate-coating system composed of an exponentially graded transversely finite layer perfectly bonded to exponentially graded transversely isotropic half-spaces. Shahmohamadi et al [32] investigated the smooth interaction of a rigid circular disk with an exponentially graded transversely isotropic coating-substrate system. In the context of functionally graded coating-substrate composite systems, several studies may be found in the literature [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Akbari et al [31] examined the static response of exponentially graded transversely isotropic substrate-coating system composed of an exponentially graded transversely finite layer perfectly bonded to exponentially graded transversely isotropic half-spaces. Shahmohamadi et al [32] investigated the smooth interaction of a rigid circular disk with an exponentially graded transversely isotropic coating-substrate system. In the context of functionally graded coating-substrate composite systems, several studies may be found in the literature [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the shear modulus of the graded interfacial layer varies as exponential function along the thickness direction. Shahmohamadi et al [19] presented a rigorous formulation for the frictionless axisymmetric interaction of a rigid disk with a two-layered inhomogeneous medium under vertical load. They considered materials are linear elastic transversely isotropic, and the exponential variation of properties along the depth of each layer was assumed in order to model the effect of inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%